Fine‐scale spatiotemporal dynamics of fungal fruiting: prevalence, amplitude, range and continuity. Issue 8 (23rd September 2016) - Heegaard, E.; Boddy, L.; Diez, J. M.; Halvorsen, R.; Kauserud, H.; Kuyper, T. W.; Bässler, C.; Büntgen, U.; Gange, A. C.; Krisai‐Greilhuber, I.; Andrew, C. J.; Ayer, F.; et al.
Abstract : Despite the critical importance of fungi as symbionts with plants, resources for animals, and drivers of ecosystem function, the spatiotemporal distributions of fungi remain poorly understood. The belowground life cycle of fungi makes it difficult to assess spatial patterns and dynamic processes even with recent molecular techniques. Here we offer an explicit spatiotemporal Bayesian inference of the drivers behind spatial distributions from investigation of a Swiss inventory of fungal fruit bodies. The unique inventory includes three temperate forest sites in which a total of 73 952 fungal fruit bodies were recorded systematically in a spatially explicit design between 1992 and 2006. Our motivation is to understand how broad‐scale climate factors may influence spatiotemporal dynamics of fungal fruiting within forests, and if any such effects vary between two functional groups, ectomycorrhizal (ECM) and saprotrophic fungi. For both groups we asked: 1) how consistent are the locations of fruiting patches, the sizes of patches, the quantities of fruit bodies, and of prevalence (occupancy)? 2) Do the annual spatial characteristics of fungal fruiting change systematically over time? 3) Are spatial characteristics of fungal fruiting driven by climatic variation? We found high inter‐annual continuity in fruiting for both functional groups. The saprotrophic species were characterised by small patches with variable fruit body counts. In contrast, ECM species were present in larger, but more distinctly delimited patches. The spatial characteristics of the fungal community were only indirectly influenced by climate. However, climate variability influenced overall yields and prevalence, which again links to spatial structure of fruit bodies. Both yield and prevalence were correlated with the amplitudes of occurrence and of fruit body counts, but only prevalence influenced the spatial range. Summarizing, climatic variability affects forest‐stand fungal distributions via its influence on yield (amount) and prevalence (occupancy), whereas fungal life‐history strategies dictate fine‐scale spatial characteristics.